Digital Identity and Ethical Challenges on Social Media: An Islamic Communication Perspective - novianto puji raharjo (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2025)
This research aims to explore and analyze the application of communication ethics in the era of social media. Using qualitative content analysis methods as well as in-depth interviews, the study found that communication ethics on social media are often ignored by users, especially in terms of the dissemination of inaccurate information, social polarization, and hate speech. Users also tend to manage their digital identities by displaying an ideal image that is different from reality, which creates social pressure and lowers the quality of communication. Ethical awareness varies among users, influenced by digital literacy and education levels. These findings emphasize the importance of stricter regulations and digital literacy education to improve communication ethics on social media. The study concludes that while social media offers opportunities for wider interaction, better regulation and social responsibility are needed to create a more ethical and responsible digital communication environment.